Buku Saku Pendidikan Politik bagi Pprapemilih Sebagai Upaya Mempersiapkan Pemilih Pemula yang Rasional - hariyanti, Hariyanti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
The purpose of writing this article is to analyze political education strategies for pre-electers as well as political education pocket books for pre-electors. This study uses a descriptive qualitative method. The results of the study show that the political education strategy for pre-voters is carried out by building cooperation between the General Election Commission and Pancasila and Citizenship Education subject teachers through the Election Smart House. Political education for pre-voters is integrated into Pancasila and Citizenship Education subjects. The political education pocket book for pre-elect discusses seven materials including material on nation, state, democracy, political education, political parties, general elections, as well as pre-electers and the need to be smart voters. The political education pocket book for prevoters is equipped with learning media in the form of a smart pre-voter card which is included at the end of the pocket book